Hormonal impact on tumor growth and progression - Reznikov, A. (Experimental Oncology, 2015)
In this review, current knowledge of hormones impact on prostate, breast and endometrium cancer growth and transition to hormone therapy resistant phenotype is summarized. A special consideration is given to genetic alterations and hormone responsive signaling pathways. Estrogen, androgen and progesterone are the key drivers in these cancer variants. Hormone receptors and their interplay with plenty of growth factors generated by the tumor microenvironment contribute greatly to carcinogenesis and cancer cell proliferation. The tumor cell plasticity that could explain a loss of responsiveness to hormone deprivation therapy and aggressive course of the diseases has been addressed. Key Words: hormone, prostate cancer, breast cancer, endometrial cancer, receptor signaling.